The Impact of Sustainability Education Mindset and Project Management Skills on Filipino Gen Z Pre-service Science Educators’ Innovative Pedagogical Disposition - Obmerga, Marwin (GILE Journal of Skills Development, 2026)
The emergence of Generation Z as future professional teachers is reshaping the educational landscape, particularly within science education. Despite their increasing presence in pre-service teacher training, limited scholarship exists on their cognitive, affective, and psychomotor dispositions, especially within developing nations of the Global South. Considering their neoliberal orientations and their pivotal role in realising Sustainable Development Goal (SDG) 4 on Quality Education, this study examined how Sustainability Education Mindset (SEM) and Project Management Skills (PMS) influence their Innovative Pedagogical Disposition (IPD). Employing a quantitative design with bivariate (correlation) and multivariate (multiple regression) analyses, the study involved 141 Gen Z pre-service science teachers across key regions in the Philippines who completed the robotfoto and standardised instruments. Results revealed significant positive associations between several SEM and PMS sub-dimensions, although some pairings showed inverse relationships, reflecting the nuanced and multifaceted nature of their professional formation. Notably, SEM dimensions such as Democratic Education and Inclusiveness in Education, alongside PMS components like Communication Skills and Managerial Competences, emerged as significant positive predictors of multiple IPD sub-dimensions. Theoretically, the findings advance understanding of how sustainability-oriented mindsets and budding managerial proficiencies coalesce to shape innovative pedagogical tendencies among emerging science educators. Practically, the study underscores the necessity of embedding sustainability and project-based skill development in teacher education curricula to nurture Gen Z educators as agents of pedagogical innovation and dynamic sustainability.